The Impact of the COVID-19 Epidemic on Orthodontic Patients in China: An Analysis of Posts on Weibo - Guo, Feiyang; Tang, Bojun; Qin, Danchen; Zhao, Tingting; Su, Yu-xiong; McGrath, Colman; Hua, Fang; He, Hong (Frontiers in Medicine, 2020)
Background: During the COVID-19 pandemic, many dental care services including orthodontic practice were suspended. Orthodontic patients turned to social media platforms to communicate, share experiences, and look for solutions. Our study aimed to investigate the attitudes and perspectives of orthodontic patients during the COVID-19 epidemic in China by analyzing orthodontics-related posts on Sina Weibo (a Chinese counterpart of Twitter). Materials and Methods: Potentially eligible posts on Sina Weibo platform were collected between December 30, 2019, and April 18, 2020. Posts related to both orthodontics and COVID-19 were included and then coded and classified into specific appliances and themes. Geographic and temporal distributions of the included posts were analyzed. In addition, time-lagged cross correlation was performed to explore the association between the number of daily posts and daily new COVID-19 cases/deaths in China. Chi-square tests were employed to compare the differences between fixed appliances and aligners in problems/difficulties and feelings during the epidemic. Results: Of the 28,911 posts identified, 4,484 were included in the analysis. The most frequently mentioned themes were appointments (n = 2,621, 58.5%), negative feelings (n = 2,189, 48.8%), and problems/difficulties (n = 1,155, 25.8%). A majority of posts were tweeted in regions with high levels of economic development and population density in eastern China and from February to March. The number of daily posts had a significantly positive correlation with daily new COVID-19 cases/deaths in China (P < 0.05). Compared with clear aligners, patients with fixed appliances reported more problems/difficulties (P < 0.001) and negative feelings (P < 0.001), but fewer positive feelings (P < 0.001). Conclusions: The analysis of Weibo posts provided a timely understanding of the impact of COVID-19 on orthodontic patients. Delayed appointments were their greatest concern, and negative feelings and untreated orthodontic problems increased during the suspension of dental care services. However, patients with clear aligners reported fewer negative feelings and problems than those with fixed appliances. The findings highlighted the need to consider both treatment- and psychology-related issues of orthodontic patients and how to handle them appropriately during the epidemic.